2020
DOI: 10.1002/agg2.20003
|View full text |Cite
|
Sign up to set email alerts
|

The performance of spring wheat cultivar mixtures under conventional and organic management in Western Canada

Abstract: Wheat (Triticum aestivum L.) cultivar mixtures may stabilize yield across environments, control air‐borne diseases, and manage pest populations in both conventional and organically managed systems. The objective of this study was to evaluate agronomic and end‐use quality characteristics of wheat cultivar mixtures. Five Canada Western Red Spring wheat cultivars (‘Go Early’, ‘Carberry’, ‘Glenn’, ‘CDC Titanium’, and ‘Lillian’) differing in agronomic and quality traits were selected to compose 20 possible two‐way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…Cowger et al (2008) and Mundt et al (1995) reported an average yield increase in winter wheat mixtures but yield increases were relatively small. Similarly, there was no significant difference between single and combination of winter wheat in the study of Chen et al (2020) of 4.06 t ha -1 . For organic spring wheat cultivation, Dai et al (2012) found that the cultivar mixture did not improve grain yield.…”
Section: Grain Yieldmentioning
confidence: 76%
See 1 more Smart Citation
“…Cowger et al (2008) and Mundt et al (1995) reported an average yield increase in winter wheat mixtures but yield increases were relatively small. Similarly, there was no significant difference between single and combination of winter wheat in the study of Chen et al (2020) of 4.06 t ha -1 . For organic spring wheat cultivation, Dai et al (2012) found that the cultivar mixture did not improve grain yield.…”
Section: Grain Yieldmentioning
confidence: 76%
“…Wheat protein content is a factor to consider when making bread, protein content varies depending on wheat variety, growing area, soil type and quality, and fertilizer input (type, amount and time), particularly nitrogen. According to Chen et al (2020), the protein content was lower in organic farming than conventional farming. Protein content was higher under mixtures of two varieties but the increases were relatively small (0.2%) compared to wheat varieties grown singly in an organic system.…”
Section: Wheat Qualitymentioning
confidence: 99%
“…The five breeding methods employed to develop cultivars for organic agriculture are the following: (i) indirect selection under conventional management, (ii) direct selection under organic management in all generations, (iii) selection under conventional management in early generations, followed by selection under organic management in advanced generations, (iv) marker-assisted selection (MAS), and (iv) genomic selection [ 4 , 14 , 15 ]. The University of Alberta Wheat Program, Edmonton, AB, has studied the pros and cons of these methods in diverse spring wheat lines and cultivars evaluated under both conventional and organic management systems, including comparing yield components [ 16 , 17 , 18 ], the performance of sole crop with mixtures [ 19 , 20 ], weed and nutrient competitive abilities [ 8 , 9 , 21 ], breadmaking quality [ 22 ], mapping genes and quantitative trait loci (QTL) associated with agronomic traits [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and comparing the prediction accuracies of different genomic selection models [ 30 , 31 ]. Recently, we reported the physical positions of 44 QTLs associated with heading, flowering, and maturity [ 26 ] and 152 QTLs associated with nine agronomic and end-use quality traits in four recombinant inbred line (RIL) populations, which were evaluated under conventional and organic management systems [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists from Western Canada [9], with intention of yield stabilizing across environments, control of air-born diseases, and manage pest populations, performed an experiment with five wheat cultivars and 20 their two-way and three-way blends, all this in four conventional and two organic environments. Cultivar mixtures may increase yield (3.3 to 14.1 %) across environments, control air-borne diseases, and manage pest populations in both conventional and organically managed systems, found them.…”
Section: Introductionmentioning
confidence: 99%
“… Compensation effects -a stronger variety compensates for a weaker or injured variety.  Better disease control due to more different resistance genes involved -management of multiple disease tolerance [3], [4], [5], [6], [7], [8], [9], [10], [11], [15], [16].  Better protection from insect attacks [14].…”
Section: Introductionmentioning
confidence: 99%